2018
DOI: 10.3390/app9010026
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Optimized Design of Metamaterials for Mid-Range Wireless Power Transfer Using a Class-E RF Power Amplifier

Abstract: Featured Application: The proposed Wireless Power Transfer (WPT) system with metamaterials using Class-E amplifier can be applied for mid-range high-power energy transfer. Abstract: In this paper, a mid-range wireless power transfer (WPT) system based on metamaterials (MMs) has been presented. It has been shown that the MMs are positioned in the WPT system to focalize the electromagnetic field for distance enhancement and efficiency improvement theoretically and experimentally. The MMs were fabricated by using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…However, it is also worth studying the MNM-MMs operating at the lower megahertz range. Rong et al [18] researched and built a set of WPT systems with MNM-MMs working at 2.8 MHz. The MNM-MM can improve the PTE by 18.58% under the best case.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is also worth studying the MNM-MMs operating at the lower megahertz range. Rong et al [18] researched and built a set of WPT systems with MNM-MMs working at 2.8 MHz. The MNM-MM can improve the PTE by 18.58% under the best case.…”
Section: Introductionmentioning
confidence: 99%
“…Rong et al [18] researched and built a set of WPT systems with MNM-MMs working at 2.8 MHz. The MNM-MM can improve the PTE by 18.58% under the best case. However, the PTE improvement obtained by using the MMs is low.…”
Section: Introductionmentioning
confidence: 99%
“…MID technology has become well-known because of its freedom of geometric design in combination with selective structuring and metallization of 3D layout. It is able to define the angle between components, stacking of chips and foaming of cavities in contrast to the traditional printed circuit boards (PCBs) that are two-dimensional one [ 6 , 7 , 8 , 9 , 10 , 11 ]. Moreover, MIDs not only reduce the number of components and the cost by the embedding parts such as connector within a single device but also may save space and shorten assembly time.…”
Section: Introductionmentioning
confidence: 99%
“…Electromagnetic metamaterials have strong magnetic field control capabilities [ 17 , 18 ]. Many studies have shown that electromagnetic metamaterials can enhance the resonant coil coupling of WPTs and solve the electromagnetic leakage problem [ 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%